P20 A comparison of disease models in Hepatocellular carcinoma to study variations within Barcelona clinic liver cancer staging to refine prognosis and clinical decision. (20th September 2022) - Balachandrakumar, Vinay; Jackson, Richard; Stern, Nick; Evans, Jonathan; Chan, Tze; O'Grady, Elizabeth; Davis, Rob; Sieberhagen, Cyril; Fenwick, Stephen; Diaz-Nieto, Rafael; Malik, Hassan; Jones, Rob; et al.
Abstract : Background: The Barcelona clinic liver cancer (BCLC) staging system has been widely used worldwide for the management of Hepatocellular carcinoma (HCC). There are not many studies to prognosticate within this system or to better guide patient management or future study design. Aims: To investigate the role of BCLC and assess impact of subdividing groups by Albumin-Bilirubin (ALBI) grade, Neutrophil-Lymphocyte ratio (NLR) and Hepatoma arterial embolization prognostic (HAP) score on survival of patients. Methods: Single centre, retrospective, cohort study of patients with HCC Results: 676 patients were identified having HCC. The aetiology of liver diseases leading to HCC was as follows: ARLD n=208, (31%); NAFLD n=161, (24%); Patients with a combination of alcohol related liver disease and viral hepatitis accounted for n=114, 19.9% of cases. and others (including genetic haemochromatosis, autoimmune hepatitis, primary biliary cholangitis etc), n=193, (28%). When sub-divided by BCLC stage, patients were as follows: BCLC 0 n=37, (5.5%); BCLC A n=133, (20%); BCLC B n =133, (20%); BCLC C n=64, (9%); and BCLC D n=307, (45%)Median overall survival of patients with ALBI grade 1= 28.3 months (95%CI 23.1–37.5) compared to ALBI grade 2= 6.4 months (95%CI 5.0–8.4), p<0.001. Median overall survival of patients with NLR <3 = 22.7 months (95%CI 18.5–27.8) compared to NLR >3 = 8 months (95%CI 6.2–9.4), p <0.001. There was significant survival difference in HAP stages among patients with HCC and patients with HAP A had better median overall survival at 40.7 months (95%CI 35.7–46.8) compared to HAP D at 1.8 months (95%CI 1.5–2.3), p<0.001. Within each stage of HCC according to BCLC staging, HAP score was able to better identify patients who would benefit from treatment (BCLC A-C) with good median survival compared to NLR and ALBI grade. Conclusion: NLR and ALBI grade was able to better differentiate survival among patients with HCC irrespective of treatments. Our study showed HAP score had a role beyond patients receiving chemo embolization, i.e., BCLC stage B in decision making of treatment for patients i.e. BCLC A-C. Algorithms can be developed to utilize prognostic scores to better individualize patient treatments and future study design. A proposed algorithm using these scores to inform treatment or trials is shown ( figure 1 ).